(untitled) (Journal of Engineering, 2003)
Simulation of naturally fractured reservoirs is a laborious techniques, because there are two different porous media in which fluids exist and flow. The porous media exhibit wide variations in their physical properties. The matrix usually represents the major storage capacity while the fractures system provides the main paths of the flowing fluids. Several simulators have been constructed by specialist companies. One is the SimBestII, which is the product of Scientific Software- Intercomp. In order to simulate a reservoir properly by such simulator, one should have an idea about the equations and the procedures encountered in it. In the present study, an attempt has been made to understand the general structure of SimBestll. The flow equations that are employed in SimBestII are investigated and some of the calculation procedures are clarified. The exchange term in the flow equations is discussed comprehensively and the justifications to reduce or magniff the imbibition rate are explored